Aluminum Chloride. Issue 3 (May 2015) - Totri, Christine R.; Jacob, Sharon E.
Abstract : ABSTRACT: By definition, a drug is a medicine or substance that exerts a physiologic affect on an organism. In dermatology, medications and substances are utilized on a daily basis from topical treatments to anesthetics in micrographic surgery. The purpose of this column is to focus on some of the more common drugs used in dermatology, specifically their mechanism of action and routine alternatives (if available). This brief focuses on the utilization of aluminum chloride in dermatologic hemostasis and provides a table of alternative caustic agents used for hemostasis.